Health Education Effect of Roleplay Method on Improvement of Self Confidence In Child Obesity Victims of Bullying (10-12 years) - Harmayetty, Harmayetty; Novita, Wahyu; Krisnana, Ilya (International Journal of Psychosocial Rehabilitation, 2020)
Obesity in children has a negative impact and influences children's growth and development, especially in aspects of psychosocial development. Short-term ef ects caused by bullying behavior are feeling insecure, embarrassed, reduced interest in learning that has an impact on academic achievement. The study was a "Pre-Experimental" research design with the pre-posttest one group design. The sampling technique uses purposive sampling. The number of research samples was 15 respondents. Data were analyzed using the Wilcoxon Signed Rank Test p ≤ 0.05and showed that role play method can increase the self-confidence in children with obesity as bullying victims (p = 0.001). Role play can make children develop the ability to think and act creatively. understand the feelings of others, put themselves out of other people's situations, understand and respect dif erences of opinion, so that they can live up to the role played, are able to put themselves in situations, learn how to get along and how to approach and relate to others.